Death and afterlife Perspectives of world religions - Ōbayashi, Hiroshi (New York Greenwood Press, 1992)
Examines the subject of death and immortality in Africa, Mesopotamia, Egypt, Greece. Also from the point of view of the Old Testament, New Testament, Judaism, Christianity, Islam, Hinduism, Buddhism and Tibetan Trantric and Chinese religions.
Keywords: Death - Religious aspects - Comparative studies